1/5x-1/6(x-4)=6x

Simple and best practice solution for 1/5x-1/6(x-4)=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/5x-1/6(x-4)=6x equation:


x in (-oo:+oo)

(1/5)*x-((1/6)*(x-4)) = 6*x // - 6*x

(1/5)*x-((1/6)*(x-4))-(6*x) = 0

(-1/6)*(x-4)+(1/5)*x-6*x = 0

x/5-1/6*(x-4)-6*x = 0

(-1/6*5*(x-4))/5+x/5+(-6*5*x)/5 = 0

x-1/6*5*(x-4)-6*5*x = 0

1/6*x-30*x+10/3 = 0

10/3-179/6*x = 0

(10/3-179/6*x)/5 = 0

(10/3-179/6*x)/5 = 0 // * 5

10/3-179/6*x = 0

10/3-179/6*x = 0 // - 10/3

-179/6*x = -10/3 // : -179/6

x = -10/3/(-179/6)

x = 20/179

x = 20/179

See similar equations:

| 2/3x-1/3x=-4 | | 2/3x-1/3=-4 | | -24.5-5k=-9.5(6k+5.5) | | 22.5=-2(5n-6.5) | | 3/13x=12 | | 8n^2-9np-14p^2=0 | | [2x-1]=5 | | x-8.2=-5.8 | | x^2-7x=7-x | | 2x^2+16x=96 | | x^4+16=8x^2 | | 17m+6+13m+42= | | t+21=14 | | [x-8]=30 | | 4.5(7r+6)=24.5+5.5r | | -1(8-1)+6= | | 3c+17-20c+33= | | 5y+2y+8y-2-4= | | 28.5=-4.5+9.5(y-5.5) | | 5p+7q=1 | | w-4/5=8/3 | | -1/3x+2=-4 | | 4y^2+8yz+3z^2=0 | | 3056890000-15000000t=3000000000 | | 4.5-8(1-8.5c)=29.5 | | a=2.598r^2 | | -7(8.5-9.5s)=18.5 | | -4/5=8/3 | | (3/4y)+(2/3)=(5/6) | | -8x-7.5+7x=-26.5 | | r=1.155r | | -8(9.5b-4)=26.5 |

Equations solver categories